2019
DOI: 10.1177/0021998319866904
|View full text |Cite
|
Sign up to set email alerts
|

Rate effects on fiber–matrix interfacial transverse debonding behavior

Abstract: The rate effect of fiber–matrix interfacial debonding behavior of SC-15 epoxy with S-2 glass and aramid fiber reinforcements was studied via in-situ visualization of the transverse debonding event. In this study, the debonding force history, debonding initiation, debonding crack velocity, and crack geometry were characterized using a quasi-static load frame and a modified tension Kolsky bar at loading velocities of 0.25 mm/s and 2.5 m/s. Cruciform-shaped specimens were used for interfacial transverse debonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Applying a high strain rate tensile load to a single fibre [28] is arguably the simplest such approach, and novel diagnostic options include imaging of a SHPB-driven experiment using a synchroton's x-ray beamline [29]. Chu et al designed a pull-apart test for a similar glass/epoxy specimen, showing that the debonding force increased by 81% from quasistatic to high strain rate loading, while the crack velocity increased by 16% [30]. There are also many examples of quasistatic fibre-matrix interface experiments, such as Favre & Merienne's pull-out assessment of fibre coatings [31].…”
Section: Testing Techniquesmentioning
confidence: 99%
“…Applying a high strain rate tensile load to a single fibre [28] is arguably the simplest such approach, and novel diagnostic options include imaging of a SHPB-driven experiment using a synchroton's x-ray beamline [29]. Chu et al designed a pull-apart test for a similar glass/epoxy specimen, showing that the debonding force increased by 81% from quasistatic to high strain rate loading, while the crack velocity increased by 16% [30]. There are also many examples of quasistatic fibre-matrix interface experiments, such as Favre & Merienne's pull-out assessment of fibre coatings [31].…”
Section: Testing Techniquesmentioning
confidence: 99%
“…For example, transverse impact on yarns [1,2], composite strips [3], composite single plies [4], fabrics [5], and laminates [6] revealed a punch-shear failure mechanism at the critical velocity or ballistic limit, indicating that fibers are not under a pure-tension stress state. Besides, fractography on several fibers after transverse debonding with matrix [7] showed that aramid fibers were split transversely during debonding. In contrast, S-2 glass fibers debonded with the matrix along their interfaces.…”
Section: Introductionmentioning
confidence: 99%